Computer system component power consumption characterization using artificial neural networks - Dolar, James V. (2012)
This study was undertaken to find a solution for predicting the power consumption of a computer system for a given work load with the intent of using this as a tool for energy planning in IT infrastructure. Using various software to simulate component work loading in the computer system, time-series performance parameters were gathered, as well as the actual lower consumption. Both the performance parameters as input and the power consumption as output, were then processed using an Artificial Neural Network (ANN) to derive the relationship between them. The ANN successfully converged to a solution after numerous training cycles. It was found that in comparison with the curve fitting method, the ANN was more accurate in 3 out of 4 validations, and is far better option when attempting to model a computer system that has more than one relevant input parameter. An application scenario was explored in order to confirm its usability in a practical problem.
"April 2012."
Thesis (M.S. in Energy Engineering)--University of the Philippines, Diliman
Keywords: Electric power consumption; Computers -- Energy consumption